1995
DOI: 10.1093/jmedent/32.3.276
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Ixodid Tick Fauna (Acari: Ixodidae) of Vietnam

Abstract: Forty-eight species making up the tick fauna of Vietnam (genera Ixodes, Ixodes, Amblyomma, Aponomma, Haemaphysalis, Dermacentor, Hyalomma, Nosomma, Rhipicephalus, Boophilus) are reviewed, including one genus and nine species that are new records for Vietnam, as well as four species described by the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 0 publications
2
44
0
Order By: Relevance
“…Both studied the temperature below which the activity of ticks is completely stopped and the temperature at which it expressed its full activity and found a significant relationship of tick activities and the degree of reduction of temperature for adult forms. This agrees with the data published about ticks in various part of Russia, Central Europe and the West Balkans (4,12,13,14,20,21,25,26,29,31).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Both studied the temperature below which the activity of ticks is completely stopped and the temperature at which it expressed its full activity and found a significant relationship of tick activities and the degree of reduction of temperature for adult forms. This agrees with the data published about ticks in various part of Russia, Central Europe and the West Balkans (4,12,13,14,20,21,25,26,29,31).…”
Section: Resultssupporting
confidence: 92%
“…During all the examinations, Ixodes ricinus was the most abundant tick species insheep and goats. The found species of ticks are most common in sheep and goats in the regions of the Western Balkans, Mediterranean and Central Europe (14,16,25,27,28,37,38,48).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amblyomma orlovi (Kolonin, 1995) is considered a valid species by Camicas et al (1998) [under the genus Aponomma], Horak et al (2002) and Barker and Murrell (2004). It was originally described from Vietnam (Kolonin 1995), but later Kolonin (2003) concluded that his specimens of A. orlovi had originated in tropical West Africa.…”
Section: Amblyomma Fuscummentioning
confidence: 99%
“…It was originally described from Vietnam (Kolonin 1995), but later Kolonin (2003) concluded that his specimens of A. orlovi had originated in tropical West Africa. While we tentatively consider A. orlovi a valid name, our reading of the original description strongly suggests that this species is a junior synonym of A. transversale (Lucas, 1844).…”
Section: Amblyomma Fuscummentioning
confidence: 99%